(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Equity in physical activity (PA) is a critical issue, with disadvantaged groups having the lowest PA levels and facing barriers to be physically active. The World Health Organization (WHO) has emphasised equity as a guiding principle of its Global Action Plan, underscoring the need to embed this principle in PA policy and practice. In recent years, various tools have been developed to monitor and assess PA policies, aiming to contribute to future policy development. One of these tools is the Physical Activity Environment Policy Index (PA-EPI) that assesses the extent of policy implementation across 45 indicators. This study aimed to develop an equity module for the PA-EPI to systematically incorporate an equity perspective into its application. Methods: The development of the PA-EPI equity module involved a four-step process: (1) Analysing key findings from a literature review on equity and PA to identify policy characteristics that affect inequities; (2) Conducting a search for additional scientific publications and key policy documents to extract equity-related guidance; (3) Drafting the PA-EPI equity module based on the extracted data, and (4) Refining and finalising the module through a series of expert workshops. Results: The PA-EPI equity module provides specific guidance for 38 of the 45 PA-EPI indicators, and is currently based on 29 studies and 25 policy documents. This new component of the tool is embedded into the evidence document template to ensure that equity-related aspects are systematically considered when using the PA-EPI. This may include the identification of PA policies targeting vulnerable groups as well as assessing the extent of their implementation. Conclusion: The PA-EPI equity module represents a novel approach to incorporating equity as a guiding principle into policy assessment tools. While it is particularly useful for researchers, stakeholders, and government officials utilising the PA-EPI, the module may also inform other initiatives by synthesising current guidance on equity and PA policy. Future research is needed to test the module’s applicability and its contribution to enhancing the equity focus in PA policy monitoring. Support/Funding Source: This is part of the project IMPAQT which is funded from Ireland, Health Research Board; Poland, National Centre for Research and Development; Germany, Federal Ministry of Education and Research; The Netherlands, The Netherlands Organisation for Health Research and Development; Romania, Executive Agency for Higher Education, Research, Development and Innovation Funding; Lithuania, Research Council of Lithuania, under the umbrella of the Partnership Fostering a European Research Area for Health (ERA4Health) (GA N° 101095426 of the EU Horizon Europe Research and Innovation Programme). Keywords: Physical activity, policy, equity, monitoring